Chronopharmacological Study Of Angiotensin-Converting Enzyme Inhibitor Ramipril In Hypertensive Patients In A Hospital: Analysis Of Efficacy And Tolerability Based On Administration Time Variations - Fendy Prasetyawan; Faisal Akhmal Muslikh; Yuneka Saristiana; Ratna Mildawati; Chandra Arifin; Abd Rofiq; Dewi Retno Puspitosari (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2024)
This research investigates the chronopharmacological effects of Ramipril administration on hypertensive patients, focusing on the timing of drug intake. Studies conducted by Firli Choerun Nisa and Siti Rohmiati in 2022 provide the basis for this analysis. Using observational-analytic methods with cross-sectional designs, data were collected prospectively from 23 patients in each study. Firli Choerun Nisa's study at RSUD Singaparna Medika Citrautama, Tasikmalaya Regency, involved 14 patients in the light zeitgeber group and 9 in the dark zeitgeber group. Results indicated significant reductions in both systolic and diastolic blood pressures, with the dark zeitgeber group experiencing more substantial decreases. The SPSS analysis showed a p-value of 0.062, indicating no statistically significant difference between the groups. Siti Rohmiati's study at RSUD Dr. Soekardjo Tasikmalaya found similar results. The light zeitgeber group showed a systolic decrease of 9.9 mmHg and a diastolic decrease of 5 mmHg, while the dark zeitgeber group had decreases of 16.66 mmHg and 10.56 mmHg, respectively. The SPSS analysis also yielded a p-value of 0.062, supporting the conclusion of no significant difference in Ramipril's efficacy based on administration timing. The comprehensive analyses revealed that Ramipril effectively reduces blood pressure regardless of the administration time. Significant reductions in both the daytime and nighttime groups were noted, with trends suggesting a more pronounced effect during nighttime administration. These findings emphasize the importance of flexibility in medication timing, enhancing patient adherence without compromising therapeutic outcomes. In conclusion, the timing of Ramipril administration, whether in the morning or evening, does not significantly impact its effectiveness in managing hypertension. This flexibility offers practical benefits for clinical practice, supporting better patient adherence and optimized hypertension management. These studies contribute to the broader understanding of chronopharmacology, providing insights for improved treatment strategies in hypertensive care.